1997
DOI: 10.1038/sj.bmt.1700881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-major histocompatibility antigens on acute graft-versus-host reaction after allogeneic bone marrow transplantation

Abstract: Summary:the GVHR preventing recurrence of leukemia, via a graftversus-leukemia (GVL) effect.In the present study, using experimental BMT in a mouse In the present study using an experimental BMT system we analyzed the effects of disparity at non-MHC Ag system we investigated the influence of mismatch at non-MHC loci on acute GVHR. We focused particularly on including minor lymphocyte stimulatory-1 a (Mls-1 a ) Ag on the acute GVH reaction (GVHR) induced by MHC minor lymphocyte stimulatory (Mls)-1 a Ags express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In addition, we previously reported that spleen cells from GVHD [B10.AQR → AKR] and [B10.BR → AKR] bone marrow chimeras produced spontaneously high levels of IL-4 at an early stage after BMT. 19 Although the precise mechanism remains unclear, it seems to us that this spontaneous IL-4 production is somehow related to the present findings obtained with [B10.A → AKR] T ϩ chimeras 8 weeks after BMT.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In addition, we previously reported that spleen cells from GVHD [B10.AQR → AKR] and [B10.BR → AKR] bone marrow chimeras produced spontaneously high levels of IL-4 at an early stage after BMT. 19 Although the precise mechanism remains unclear, it seems to us that this spontaneous IL-4 production is somehow related to the present findings obtained with [B10.A → AKR] T ϩ chimeras 8 weeks after BMT.…”
Section: Discussionsupporting
confidence: 68%
“…44,45 However, in our previous study, 19,24 no significant population of NK-T cells was detected, but V␤6 ϩ ordinary T cells increased markedly in the spleens and thymuses of GVHD chimeras at an early stage after BMT. These findings suggest that the increased V␤6 ϩ , perhaps CD4 ϩ , T cells are responsible for the Th2 shift.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-␥ in the culture supernatants was quantitated with Cytoscreen Immunoassay kit for mouse IFN-␥ (BioSource International). 37 …”
Section: Cytokine Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%